2000
DOI: 10.1038/sj.cgt.7700202
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LNCaP prostate cancer cells by means of androgen receptor antisense oligonucleotides

Abstract: Currently available methods for treatment of human prostatic carcinoma aim to inactivate the androgen receptor (AR) by androgen deprivation or blockade with anti-androgens. Failure of endocrine therapy and tumor progression is characterized by androgenindependent growth despite high levels of AR expression in metastatic disease. We inhibited AR expression in LNCaP prostate tumor cells by using antisense AR oligodeoxynucleotides (ODNs) and explored whether antisense AR treatment would be conceivable as a therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 38 publications
5
105
0
3
Order By: Relevance
“…Similar results were also reported by Liao et al [14] and Haag et al [15]. Eder et al [16] inhibited AR expression in LNCaP cells using antisense AR oligodeoxynucleotides and reduced AR expression to approximately 2% of normal levels within 24 h. They found that down-regulating AR significantly inhibited LNCaP cell growth, strongly reduced secretion of the androgen-regulated prostatespecific antigen and increased the level of cell apoptosis [16]. Eder et al [17] further investigated the effects of AR knockdown on prostate tumor growth in vivo using a mouse xenograft model.…”
Section: Lncap Cellssupporting
confidence: 90%
“…Similar results were also reported by Liao et al [14] and Haag et al [15]. Eder et al [16] inhibited AR expression in LNCaP cells using antisense AR oligodeoxynucleotides and reduced AR expression to approximately 2% of normal levels within 24 h. They found that down-regulating AR significantly inhibited LNCaP cell growth, strongly reduced secretion of the androgen-regulated prostatespecific antigen and increased the level of cell apoptosis [16]. Eder et al [17] further investigated the effects of AR knockdown on prostate tumor growth in vivo using a mouse xenograft model.…”
Section: Lncap Cellssupporting
confidence: 90%
“…Consequently, restoration of normal AR expression/function may prove to be an effective mean of treatment in this stage of the disease. This concept is supported by recent observations that downregulation of AR expression by means of AR antisense oligos, or disruption of AR function via direct injection of AR antibody into cells, produced significant inhibition of proliferation of the refractory PC cells, and induced apoptosis (Eder et al, 2000;Zegarra-Moro et al, 2002).…”
Section: Introductionmentioning
confidence: 74%
“…Because the AR is clearly a critical factor in prostate cancer and AIPC development, down-regulating or reducing the AR would be a very useful strategy for treating ARdependent prostate cancer (8). Thus far, the techniques that have been used to down-regulate the AR include antisense oligonucleotides (34,35), ribozyme treatments (36, 37), AR dominant negatives (38), and small interfering RNAs (39 -41). Reducing AR levels by these various means results in the inhibition of prostate cancer cell growth and PSA expression, while the small interfering RNA knockdown of AR expression also leads to significant apoptotic cell death in androgen-sensitive and AIPC cells (39 -41).…”
Section: Discussionmentioning
confidence: 99%